1998
DOI: 10.1093/emboj/17.15.4249
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and tissue forms of the C-terminal globular domain of collagen XVIII containing the angiogenesis inhibitor endostatin

Abstract: The C-terminal domain NC1 of mouse collagen XVIII (38 kDa) and the shorter mouse and human endostatins (22 kDa) were prepared in recombinant form from transfected mammalian cells. The NC1 domain aggregated non-covalently into a globular trimer which was partially cleaved by endogenous proteolysis into several monomers (25-32 kDa) related to endostatin. Endostatins were obtained in a highly soluble, monomeric form and showed a single N-terminal sequence which, together with other data, indicated a compact foldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
329
0
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(352 citation statements)
references
References 46 publications
19
329
0
4
Order By: Relevance
“…The consistent observation of NC1 trimerization and other biochemical data led to the proposal of a segmental NC1 structure (20). At the N-terminus there is an association domain of about 60 residues probably including a short telopeptide connection to the triple-helix; at the C-terminus there is the 180-residue endostatin module (Fig.…”
Section: Structure and Binding Properties Of Nc1 Domains And Endostatinssupporting
confidence: 54%
See 3 more Smart Citations
“…The consistent observation of NC1 trimerization and other biochemical data led to the proposal of a segmental NC1 structure (20). At the N-terminus there is an association domain of about 60 residues probably including a short telopeptide connection to the triple-helix; at the C-terminus there is the 180-residue endostatin module (Fig.…”
Section: Structure and Binding Properties Of Nc1 Domains And Endostatinssupporting
confidence: 54%
“…Soluble monomeric endostatins could be obtained, however, from insect cells (4), yeast (17,19), and mammalian cells (20)(21)(22) but they may show subtle differences in conformation and posttranslational modifications. Domain NC1 could be also produced in mammalian cells and was shown to assemble noncovalently into a 100-kDa homotrimer as demonstrated for mouse collagens XVIII (20) and XV (21) and the C. elegans homolog (15).…”
Section: Structure and Binding Properties Of Nc1 Domains And Endostatinsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies identified secreted cathepsin L as an enzyme capable of generating endostatin, whereas the matrix metalloproteases produce larger fragments in an alternate pathway . In vivo, proteolytic processing of collagen XVIII can generate both the NC1 trimer and the 20 kDa endostatin monomer (Sasaki et al, 1998;Wen et al, 1999) since both fragments are found in tissues and serum (Standker et al, 1997;John et al, 1999). In vitro, the NC1 fragment is more sensitive to proteolytic degradation than 20 kDa endostatin (Ferreras et al, 2000).…”
mentioning
confidence: 99%